Evolution of Echocardiography-Derived Hemodynamic Force Parameters After Cardiac Resynchronization Therapy - Laenens Dorien; van der Bijl Pieter; Galloo Xavier; Rossi Alessandro C; Tonti Giovanni; Reiber Johan H; Pedrizzetti Gianni; Ajmone Marsan Nina; Bax Jeroen J (Elsevier Inc., 2025)
Echocardiography-derived hemodynamic forces (HDF) allow calculation of intraventricular pressure gradients from routine transthoracic echocardiographic images. The evolution of HDF after cardiac resynchronization therapy (CRT) has not been investigated in large cohorts. The aim was to assess HDF in patients with heart failure implanted with CRT versus healthy controls. HDF were assessed before and 6 months after CRT. The following HDF parameters were calculated: (1) apical-basal strength, (2) lateral-septal strength, (3) the ratio of lateral-septal to apical-basal strength ratio, and (4) the force vector angle (1 and 2 representing the magnitude of HDF, 3 and 4 representing the orientation of HDF). In the propulsive phase of systole, the apical-basal impulse and the systolic force vector angle were measured. A total of 197 patients were included (age 64 ± 11 years, 62% male), with left ventricular ejection fraction ≤35%, QRS duration ≥130 ms and left bundle branch block. The magnitude of HDF was significantly lower and the orientation was significantly worse in patients with heart failure versus healthy controls. Immediately after CRT implantation, the apical-basal impulse and systolic force vector angle were significantly increased. Six months after CRT, improvement of apical-basal strength, lateral-septal to apical-basal strength ratio and the force vector angle occurred. When CRT was deactivated at 6 months, the increase in the magnitude of apical-basal HDF remained unchanged while the systolic force vector angle worsened significantly. In conclusion, HDF in CRT recipients reflect the acute effect of CRT and the effect of left ventricular reverse remodeling on intraventricular pressure gradients. Whether HDF analysis provides incremental value over established echocardiographic parameters, remains to be determined.